Genome-wide analysis of long noncoding RNA profiling in PRRSV-infected PAM cells by RNA sequencing - Jing Zhang (Nature Portfolio, 2017)
Abstract Porcine reproductive and respiratory syndrome (PRRS) is a major threat to the global swine industry and causes tremendous economic losses. Its causative agent, porcine reproductive and respiratory syndrome virus (PRRSV), primarily infects immune cells, such as porcine alveolar macrophages and dendritic cells. PRRSV infection results in immune suppression, antibody-dependent enhancement, and persistent infection. Highly pathogenic strains in China cause high fever and severe inflammatory responses in the lungs. However, the pathogenesis of PRRSV is still not fully understood. In this study, we analysed the long noncoding RNA (lncRNA) and mRNA expression profiles of the HP-PRRSV GSWW15 and the North American strain FL-12 in infected porcine alveolar macrophages (PAMs) at 12 and 24 hours post-infection. We predicted 12,867 novel lncRNAs, 299 of which were differentially expressed after viral infection. The Gene Ontology (GO) and Kyoto Encyclopaedia of Genes and Genomes (KEGG) analyses of the genes adjacent to lncRNAs showed that they were enriched in pathways related to viral infection and immune response, indicating that lncRNAs might play regulatory roles in virus-host interactions. Our study provided information about lncRNAs in the porcine immune system and offers new insights into the pathogenic mechanism of PRRSV infection and novel antiviral therapy development.